2022
DOI: 10.3390/ijms23115947
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolic Study of Two Contrasting Chinese Cabbage Genotypes under Mild and Severe Drought Stress

Abstract: Chinese cabbage (Brassica rapa L. ssp. pekinensis) is an important leafy vegetable crop cultivated worldwide. Drought is one of the most important limiting factors for the growth, production and quality of Chinese cabbage due to its weak drought tolerance. In order to deepen the understanding of drought stress response in Chinese cabbage, metabolomics studies were conducted in drought−tolerant (DT) and drought−susceptible (DS) genotypes of Chinese cabbage under water deficit−simulated mild and severe drought s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…P5C5 has been shown to regulate proline synthesis ( Kubala et al, 2015 ) and the expression abundance of P5C5 lower in overexpression transgenic plants and m 6 A enrichment level was no significant difference ( Supplementary Figure S6 ). Proline is a key marker for drought stress response in plants ( Chen et al, 2022 ), so we compared the drought resistance between WT and transgenic lines. The results showed that overexpression of PagALKBH9B and PagALKBH10B increased the sensitivity of transgenic lines to drought stress ( Supplementary Figure S7A ).…”
Section: Resultsmentioning
confidence: 99%
“…P5C5 has been shown to regulate proline synthesis ( Kubala et al, 2015 ) and the expression abundance of P5C5 lower in overexpression transgenic plants and m 6 A enrichment level was no significant difference ( Supplementary Figure S6 ). Proline is a key marker for drought stress response in plants ( Chen et al, 2022 ), so we compared the drought resistance between WT and transgenic lines. The results showed that overexpression of PagALKBH9B and PagALKBH10B increased the sensitivity of transgenic lines to drought stress ( Supplementary Figure S7A ).…”
Section: Resultsmentioning
confidence: 99%
“…Serine is essential for the cell proliferation necessary for plant growth and development [ 66 ]. Dehydroascorbic acid participates in the regulation of ROS homeostasis during plant responses to abiotic stresses [ 67 ], whereas choline alfoscerate is a potential biomarker of abiotic stress responses [ 68 ] while also serving as an important nutrient source [ 69 ]. These enriched gene-metabolite networks may have crucial functions that contribute to the allantoin-mediated salt stress tolerance of rice.…”
Section: Discussionmentioning
confidence: 99%
“…The high sensitivity, throughput, wide coverage, and fast separation capabilities of metabolomics analyses have led to their widespread use in plant research. Metabolomic analyses have identified key metabolites in tomato [36], cabbage [37], and crops in the Triticeae family [38][39][40].…”
Section: Introductionmentioning
confidence: 99%